2021
DOI: 10.3389/fonc.2021.777760
|View full text |Cite
|
Sign up to set email alerts
|

A Bounding Box-Based Radiomics Model for Detecting Occult Peritoneal Metastasis in Advanced Gastric Cancer: A Multicenter Study

Abstract: PurposeTo develop a bounding box (BBOX)-based radiomics model for the preoperative diagnosis of occult peritoneal metastasis (OPM) in advanced gastric cancer (AGC) patients.Materials and Methods599 AGC patients from 3 centers were retrospectively enrolled and were divided into training, validation, and testing cohorts. The minimum circumscribed rectangle of the ROIs for the largest tumor area (R_BBOX), the nonoverlapping area between the tumor and R_BBOX (peritumoral area; PERI) and the smallest rectangle that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…Regarding GC, only in recent years has there been a surge of papers in the scientific literature, where radiomics has been applied in different clinical settings. These settings include prognostic stratification ( 86 89 ), prediction of peritoneal lesions ( 90 93 ), assessment of response to neoadjuvant treatments ( 54 , 94 , 95 ), prediction of peculiar biological and molecular factors ( 96 100 ), and prediction of post-operative complications ( 101 , 102 ). Within this framework, the prediction of LNM through radiomics-based tools represents one of the most explored opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding GC, only in recent years has there been a surge of papers in the scientific literature, where radiomics has been applied in different clinical settings. These settings include prognostic stratification ( 86 89 ), prediction of peritoneal lesions ( 90 93 ), assessment of response to neoadjuvant treatments ( 54 , 94 , 95 ), prediction of peculiar biological and molecular factors ( 96 100 ), and prediction of post-operative complications ( 101 , 102 ). Within this framework, the prediction of LNM through radiomics-based tools represents one of the most explored opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that peritumoral information could improve the model performance on invasiveness prediction of ADC ( 13 ) and histological subtype stratification in patients with NSCLC ( 14 ). Another previous radiomics studies reported that bounding-box delineation of ROI could achieve equivalent performance to precisely annotated ones ( 15 ). Considering the potential advantages of peritumoral areas in histologic classification tasks, in addition to the DL-aided manual-correction annotation strategy, we further explored the pixel-expansion annotation strategy for radiomics modeling by expanding lesion contours based on manual corrected ones.…”
Section: Methodsmentioning
confidence: 97%
“…Two months after image annotation, the above procedures were repeated by reader 1 and another abdominal radiologist (reader 2 [C.J.F.] with six years of experience) using 30 ( 34 ) randomly selected images. First, the ROIs of 30 patients were manually contoured, and the radiomic features of MROI1, MROI2, MROI3, IROI1, IROI2, and IROI3 were automatically obtained for each patient.…”
Section: Methodsmentioning
confidence: 99%